Lotus (Nelumbo nucifera): a multidisciplinary review of its aesthetic, ecological, and medicinal significance – A review - GUPTA, SACHI; PANT, POOJA; SINDHU, S.S. (Journal of Ornamental Horticulture, 2025)
Nelumbo nucifera, commonly known as lotus, is a plant deeply intertwined with human botanical, ecological, and nutraceutical. This paper presents a comprehensive review of the multidimensional significance of Nelumbo nucifera, spanning across various disciplines. Culturally, the lotus holds symbolic importance in numerous civilizations, depicted in art, religion, and literature. Botanical, its phytochemical composition, structural characteristics, and medicinal properties have been extensively studied, revealing its potential as a source of bioactive compounds with therapeutic benefits. Ecologically, Nelumbo nucifera plays a crucial role in aquatic ecosystems, contributing to biodiversity and habitat health. Furthermore, its nutritional value, particularly in terms of rhizomes and seeds, makes it a promising candidate in the realm of nutraceuticals. Through a multidisciplinary lens, this review aims to provide a holistic understanding of Nelumbo nucifera, highlighting its diverse significance and potential applications in various fields.